Cellular Factors Involved in HTLV-1 Entry and Pathogenicit - Hoshino, Hiroo (Frontiers in Microbiology, 2012)
Human T-cell leukemia virus type 1 (HTLV-1) is the causative agent of adult T cell leukemia (ATL) and HTLV-1–associated myelopathy and tropical spastic paraparesis (HAM/TSP). HTLV-1 has a preferential tropism for CD4 T cells in healthy carriers and ATL patients, while both CD4 and CD8 T cells serve as viral reservoirs in HAM patients. HTLV-1 has also been detected other cell types, including monocytes, endothelial cells, and dendritic cells. In contrast to the limited cell tropism of HTLV-1 in vivo, the HTLV receptor appears to be expressed in almost all human or animal cell lines. It remains to be examined whether this cell tropism is determined by host factors or by HTLV-1 heterogeneity. Unlike most retroviruses, cell-free virions of HTLV-1 are very poorly infectious. The lack of completely HTLV-1-resistant cells and the low infectivity of HTLV-1 have hampered research on the HTLV entry receptor. Entry of HTLV-1 into target cells is thought to involve interactions between the env (Env) glycoproteins, a surface glycoprotein (SU) and a transmembrane glycoprotein (TM). Recent studies have shown that glucose transporter GLUT1, heparan sulfate proteoglycans (HSPGs) and neuropilin-1 1 (NRP-1) are the three proteins important for the entry of HTLV-1. Studies using adherent cell lines have shown that GLUT1 can function as a receptor for HTLV. HSPGs are required for efficient entry of HTLV-1 into primary CD4 T cells. NRP-1 is expressed in most established cell lines. Further studies have shown that these three molecules work together to promote HTLV-1 binding and fusion of viral and cell membranes. The virus could first contact with HSPGs and then form complexes with NRP-1, followed by association with GLUT1. It remains to be determined whether HTLV-1 cell tropism can be explained by these three molecules. It also remains to be more definitively proven that these molecules are sufficient to permit HTLV-1 entry into completely HTLV-1-resistant cells.